Neoproterozoic and Early Paleozoic magmatism in the eastern Lhasa terrane: Implications for Andean-type orogeny along the northern margin of Rodinia and Gondwana - Chen, Y; Zhang, Z; Chen, X; Palin, RMM; Tian, Z; Shao, Z; Qin, S; Yuan, Y (Elsevier, 2021)
Precambrian and Early Paleozoic magmatic activities in the Lhasa terrane provides important context for distinguishing between the North and South Lhasa terranes, and deciphering the nature and geotectonic history of the northern margin of the Rodinia and Gondwana supercontinents. Here, we conducted a detailed petrological, geochemical, and geochronological study of mafic to granitic meta-intrusive rocks of the Bomi complex in the eastern segment of the Lhasa terrane. Zircon U–Pb dating indicates that these rocks record Neoproterozoic and Cambrian magmatic events, with protolith crystallization ages of ca. 805 Ma, ca. 505 Ma, and ca. 503 Ma for dioritic gneisses, amphibolites (meta-gabbros), and granitic gneisses, respectively. These rocks were later metamorphosed during the Late Jurassic, with zircon U–Pb ages of ca. 158 Ma obtained from the amphibolites. All rocks are enriched in Rb, U and LREEs, and depleted in Nb, Ta, Sr and HREEs, showing affinity with arc-related magmas. With positive zircon εHf(t) values of +1.4 to +6.9, the Neoproterozoic dioritic gneisses are interpreted to have formed by fractional crystallization of mantle-derived magmas. Cambrian amphibolites have εHf(t) values of –3.0 to +6.0, differing from those of coeval granitic gneisses (+0.3 to +3.2). These amphibolites are interpreted to have been derived from partial melting of enriched continental lithospheric mantle with contamination of subducted sediments, whereas the granitic gneisses probably originated from anatexis of lower crust that was induced by coeval emplacement of mantle-derived magma. These rocks are interpreted to be formed in a continental arc setting. When comparing these data with those of other Precambrian and Cambrian magmatic rocks in the Lhasa terrane and other blocks, we propose that the North Lhasa terrane and South Lhasa terrane have distinctive Precambrian basements. The North Lhasa terrane diachronically witnessed an Andean-type orogeny along the northwestern margin of Rodinia during the Neoproterozoic and the northeastern margin of Gondwana during the Early Paleozoic.